2017
DOI: 10.1002/ece3.2703
|View full text |Cite
|
Sign up to set email alerts
|

Growth‐form and spatiality driving the functional difference of native and alien aquatic plants in Europe

Abstract: Trait‐based approaches are widely used in community ecology and invasion biology to unravel underlying mechanisms of vegetation dynamics. Although fundamental trade‐offs between specific traits and invasibility are well described among terrestrial plants, little is known about their role and function in aquatic plant species. In this study, we examine the functional differences of aquatic alien and native plants stating that alien and native species differ in selected leaf traits. Our investigation is based on… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
13
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 40 publications
(19 citation statements)
references
References 72 publications
(98 reference statements)
3
13
1
Order By: Relevance
“…Baattrip-Pedersen et al [23] recently showed that species with high morphology index were positively associated with high phosphate levels indicating that high nutrient availability promoted those plants. Although leaf area is considered a key characteristic that is linked with ecological strategies [48], we did not find strong evidence that highlights its significance. Leaf area had a small contribution to the total variance although plants of macrophyte assemblages (Groups 1 and 3) were associated with the eigenvector of leaf area, as shown in the RLQ ordination graph.…”
Section: Discussioncontrasting
confidence: 75%
See 2 more Smart Citations
“…Baattrip-Pedersen et al [23] recently showed that species with high morphology index were positively associated with high phosphate levels indicating that high nutrient availability promoted those plants. Although leaf area is considered a key characteristic that is linked with ecological strategies [48], we did not find strong evidence that highlights its significance. Leaf area had a small contribution to the total variance although plants of macrophyte assemblages (Groups 1 and 3) were associated with the eigenvector of leaf area, as shown in the RLQ ordination graph.…”
Section: Discussioncontrasting
confidence: 75%
“…This could be associated with the increased nutrient availability (phosphorus in our case) that promotes larger vegetative and reproductive structures as reported recently by Garcia-Giron et al [47] who attributed larger vegetative and reproductive structures (in their case larger fruit size) to higher concentrations of total phosphorus. In addition, plants with larger morphology index can formulate denser and larger beds inhibiting other species in the competition for light [48]. Baattrip-Pedersen et al [23] recently showed that species with high morphology index were positively associated with high phosphate levels indicating that high nutrient availability promoted those plants.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, Pierce, Brusa, Sartori, and Cerabolini () and Lukács et al. () demonstrated that not all aquatic plants lie at the acquisitive end of the leaf economics spectrum. In general, species with low SLA are geared for the conservation of acquired resources (Cornelissen et al., ).…”
Section: Discussionmentioning
confidence: 99%
“…Successful invaders have also been suggested to have fewer enemies (Keane & Crawley ) and to be better competitors than native species (Vilà & Weiner ; Lukács et al . ).…”
Section: Introductionmentioning
confidence: 97%